Study of antioxidant and anti-inflammatory crude methanol extract and fractions of Acacia seyal gum - Elnour, Ahmed; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Musa, Khalid Hamid (iMedPub Journals, 2018)
Acacia seyal gum (ASG) is a dried exudate from tropical plants in the family Leguminosae. It has been used in the medication of eczema, inflammation, renal failure, and hypertension in folk medicine. This study presents methanol crude extracts (MCE) and different fractions of ASG in the form of raw (ASG) and commercial type Prebio-T, (PTC) using different solvents. Evaluations were performed to observe the biological activities of the extracts and fractions with certain bioassays procedure of anti-inflammatory, total phenolic content (TPC) and radical scavenging activity (DPPH). The only MCE was assessed against inflammatory reaction using carrageenan paw oedema (in-vivo). However, the antioxidant activities of MCE and its fractions were evaluated. As a result, the highest amount of TPC was observed in the Prebio-T, with an average of 694.68 ± 3.60 mgTE/100 g DW, compared to only 155.78 ± 2.58 mg TE/100 g DW for ASG Crude Extract. The highest DPPH value was seen in methanol fraction (MF) was 235.34 ± 1.57 mg TE/100 g DW for Prebio-T, compared to ASG without any significant differences (p ≤ 0.05). Both MCE of ASG and Prebio-T at 150 mg/kg dosage developed a mean and maximum percentage inhibition of 23.63% and 23.54% respectively, during the 24h observation of the acute inflammatory test. The chemical composition of the 57 phenolic compounds in methanol crude extract (MCE), and its active fractions were detected using GC-MS/MS. The major constituents in the ASG and Prebio-T MCE were iso vitamin C (42.37%), crypton (5.86%), hydroquinone (4.86%), triacetic acid lactone (2.67%), 2,4-Di-tert-butyl phenol (2.67%), cyanidin cation (2.05%), apigenin 7-glucoside (1.9%), benzoic acid (1.83%), (+)-α-tocopherol (1.58%), methyl catechol (1.42%), and 2,6-dimethylol-p-cresol (2.16%). The PBT methanolic crude extract (MCE) was found to be the most potent inhibitor of oedema formation by inducing a maximum inhibitory effect of 23.54% at the 300 mg/kg dose, during 24h post-carrageenan injection. Both PBT and ASG methanolic crude extracts showed good anti-inflammatory activities at the same dose (300 mg/kg). The results of these studies support the potential use of ASG for treating inflammation.